Emerging Vulnerabilities and Risks in Therapy Manufacture: Cell and Gene Therapy Production as an Emerging Domain of Critical Infrastructure - Edison Bicudo; Irina Brass; Herwig C.H. Hofmann; Felix Pflücke (European Journal of Risk Regulation)
Cell and gene therapies derive from a substantial manipulation of cells or the application of gene editing techniques. They are promising products because they enable therapy personalisation, are potentially helpful for treating rare or resistant diseases, and may become useful in future epidemics. Because of this strategic worth, the infrastructure needed for manufacturing these therapies is turning into a subdomain within the domain of critical infrastructures (CIs), understood as the structures whose operation is key for the integrity and security of a nation. This paper analyses why cell and gene therapy infrastructure can be considered as an emergent CI domain, stressing three aspects: automated manufacturing equipment; software solutions (including the growing adoption of artificial intelligence and cloud technology); and human expertise. These complex manufacturing systems, which are becoming increasingly automated and digitalised, may be surrounded by new risks and vulnerability points, which requires adequate regulatory solutions and governance initiatives. A comprehensive approach is therefore advanced here, where therapy manufacture has medical and technological relevance, but is equally crucial from the viewpoint of nations’ public health and internal stability.